Dental anomalies in orthodontic patients with and without skeletal discrepancies - Clarissa Christina Avelar Fernandez; Mônica Gentil Mattos; Christiane Vasconcellos Cruz Alves Pereira; Marcelo de Castro Costa (University Library System, University of Pittsburgh, 2020)
Objective:To determine whether individuals withskeletal discrepancies of Class II or IIIdisplay a higher frequency of dental anomalies in comparison with individuals with Class I malocclusion.  Design:A systematic search of the main electronic medical scientific literaturedatabases was conducted. Observational studies were selected if mentioning dental anomalies in the different skeletal malocclusion patterns. Results:A total of 4,768 studies were found and the duplicated studies (1,279) were removed, resulting in 3,489 papers to be analyzed. After screening by title, 138 were fit for screening by abstract. After that, a total of 13 papers were carefully read in full. Five studies included dental anomaly frequencies in orthodontic patients and included 7,679 participants. The frequency of dental anomalies ranged from 11.2% to 40.3%.It was observed that individuals with skeletal discrepancies of Class II and III had more dental anomalies when compared to individuals with Class I. Conclusion:Individuals with skeletal malocclusion patternshave more dental anomalies and there is an association between dental anomalies and skeletal Class II or Class III malocclusion patterns.